1992
DOI: 10.1111/j.1469-7610.1992.tb00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Adjustment among Intellectually Gifted Adolescents: the Role of Cognitive‐Developmental and Experiential Factors

Abstract: Levels of psychological adjustment were examined among 51 high achieving, intellectually gifted adolescents with a mean age of 14.1 years. These students were compared with older adolescents matched with them on cognitive maturity (n = 30), and with two groups matched with them on chronological age (CA). One of the CA-matched groups contained children not identified as gifted (n = 47), while the other consisted of athletically talented youngsters (n = 39). All participants belonged to upper middle class famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 38 publications
2
12
0
1
Order By: Relevance
“…Students with high mathematical ability may be less likely to have the opportunity brought by these classes to increase these dimensions. This hypothesis is generally compatible with Luthar et al 's (1992) discussion of schemas and how they may moderate the relationship between intelligence and psychosocial adjustment. Students of high mathematical ability, though generally more able to create schemas when properly nurtured, are less likely to take those classes which provide this opportunity for growth.…”
Section: Sat Mathsupporting
confidence: 69%
See 1 more Smart Citation
“…Students with high mathematical ability may be less likely to have the opportunity brought by these classes to increase these dimensions. This hypothesis is generally compatible with Luthar et al 's (1992) discussion of schemas and how they may moderate the relationship between intelligence and psychosocial adjustment. Students of high mathematical ability, though generally more able to create schemas when properly nurtured, are less likely to take those classes which provide this opportunity for growth.…”
Section: Sat Mathsupporting
confidence: 69%
“…Luthar et al (1992) suggested that a positive relationship between intelligence and the number of cognitive schemas produced by an individual would lead the more intelligent to categorize their experiences into a greater number of existing schemas, leading to better adjustment. This may explain divergency of thought (e.g., more schemas allowing for multiple ways to interpret and synthesize information), but this model alone, however, does not appear to be sufficient to explain other qualities (e.g., sensitivity) observed by Lovecky.…”
Section: Distal Causes Of Intelligence-based Differences In Psychologmentioning
confidence: 99%
“…In America, though, gifted girls have been found to be more depressed than gifted boys, often underestimating their abilities because of con¯icts between success and``femininity'' (Luthar et al, 1992).…”
Section: Emotional Changesmentioning
confidence: 99%
“…However, mentoring and action to improve self-esteem have been found to be effective in promoting a more realistic presentation of girls' abilities (Arnold & Subotnik, 1994). Intellectually gifted girls have been found to be more depressed than equally able boys, possib y due to the conflicts and stresses surrounding female success, although they were happier than less-able girls (Luthar, Zigler, & Goldstein, 1992). What is more, while boys tend to react to failure by becoming disruptive, the tendency of girls is to become withdrawn, and so it is the boys' response which is likely to attract most teacher attention (Galloway & Goodwin, 1987).…”
Section: Stress Producersmentioning
confidence: 99%